2009
DOI: 10.1667/rr1890.1
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation-Time Determination from Continuous-Microwave Saturation of EPR Spectra

Abstract: Based on the theories of Portis and of Castner 50 years ago, different continuous-wave measurement procedures for analyzing the microwave saturation power dependence of inhomogeneously broadened EPR lines were developed. Although these procedures have been refined, they still use only a few selected points on the saturation curve. A non-linear least-squares procedure for analyzing the microwave-power dependence of inhomogeneously broadened lines using all data points on a saturation curve has been developed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…This procedure provides a simple alternative method to obtain spin-lattice (T 1 ) or spin-spin (T 2 ) relaxation data when direct-pulse-saturation EPR techniques are not available or are less suitable. 14,46 In EPR spectroscopy, it is well known that 47 easy-to-saturate systems have generally long relaxation times, whereas hard-tosaturate systems have short relaxation times. From the microwave power-dependent measurements, it was seen that the GF defect centers were highly steady due to its easy saturation behavior, with an inhomogeneous broadening of the Gaussian line shape.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure provides a simple alternative method to obtain spin-lattice (T 1 ) or spin-spin (T 2 ) relaxation data when direct-pulse-saturation EPR techniques are not available or are less suitable. 14,46 In EPR spectroscopy, it is well known that 47 easy-to-saturate systems have generally long relaxation times, whereas hard-tosaturate systems have short relaxation times. From the microwave power-dependent measurements, it was seen that the GF defect centers were highly steady due to its easy saturation behavior, with an inhomogeneous broadening of the Gaussian line shape.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, passage effects can distort the signal shape if the spin packets cannot relax between modulation cycles. This was avoided by choosing a sufficiently small modulation amplitude B m or frequency ω m so that ω m B m <<1/( γ e T 1 T 2 ) and the spin system remains continually in thermal equilibrium30.…”
Section: Methodsmentioning
confidence: 99%
“…These observations suggest that the carbon-centered radical is responsible for the overlapping of peaks and affects the relaxation times, T1 and T2. The relaxation times were also calculated theoretically using the CW-ESR parameter (Lund, 2009). We revealed that T1 and T2 from pulsed-ESR and CW-ESR were changed similarly before and after irradiation.…”
Section: Relaxation Times T1 and T2mentioning
confidence: 91%
“…To determine T1 and T2, we used Lund's program (Lund, 2009). For a Gaussian envelope of Lorentzian spin packets, previous treatments have shown the EPR line shape can be expressed as…”
Section: Observation Of Relaxation Times Of Cw-esrmentioning
confidence: 99%